Preparation method of Cu1 / CeO2 monatomic catalyst, monatomic catalyst and application thereof
Patent Information
- Application Number
- CN202611207872.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]目前,用于电催化产H*的催化剂主要为Pt、Pd、Ru等贵金属材料,其活性高且H*生成速率快,但成本高、资源稀缺,且在复杂水体系中易中毒失活,限制了其在水污染治理中的大规模应用
[0078]本发明所述的催化剂通过金属(铜)单原子位点与可还原性载体(CeO2)的协同作用不仅显著提高了活性氢的生成效率和迁移能力,还增强了硝基官能团的选择性还原速率,降低了副反应发生的可能性。此外,该催化剂结构在长期水处理过程中表现出优异的稳定性和耐久性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalytic functional materials technology, and in particular to a method for preparing a Cu1 / CeO2 single-atom catalyst, the single-atom catalyst itself, and its applications. Background Technology
[0002] Nitro aromatic compounds (NACs) are widely used in industries such as dyes, pharmaceuticals, explosives, and pesticides. However, their high toxicity, poor biodegradability, and environmental persistence lead to their easy residue in wastewater, posing a threat to the ecological environment and human health, and thus they are listed as key controlled pollutants. The benzene ring and the strongly electron-withdrawing -NO2 group in the NAC molecule give it high chemical stability and strong antioxidant properties, making it difficult to biodegrade. By destroying or removing the -NO2 functional group, its molecular stability can be significantly reduced, thereby achieving the effective degradation of this type of pollutant.
[0003] Currently, reduction methods for recalcitrant pollutants in the environment mainly include chemical reducing agent methods, precious metal catalytic hydrogenation methods, and biological reduction methods. Chemical reducing agent methods (such as NaBH4, hydrazine, and phosphites) have relatively fast reaction rates, but suffer from high costs, high toxicity, and persistent residues. Precious metal catalytic hydrogenation methods (such as Pd / C+H2) are highly efficient, but require high temperature and pressure conditions and external hydrogen gas; they also suffer from severe dependence on precious metals and are prone to poisoning or agglomeration and deactivation. Biological reduction methods, while having better environmental adaptability, are slow and highly susceptible to temperature, pH, and electron donor concentration, making scale-up difficult. In summary, existing reduction methods generally suffer from high energy consumption, high costs, poor selectivity, or high potential pollution risks, making it difficult to meet the demands for efficient and green water pollution control. Therefore, there is an urgent need to develop new, green, low-cost, and highly selective electrochemical reduction denitrification methods.
[0004] Electrocatalytic reduction is a green and efficient method for pollutant removal, with several advantages: the reaction can be carried out at room temperature and atmospheric pressure, ensuring high safety; the reaction is driven by electricity, eliminating the need for external chemical reducing agents; the reduction selectivity can be precisely controlled by adjusting the potential, achieving in-situ degradation and highly selective reduction of pollutants with few byproducts; furthermore, this method can be coupled with renewable energy sources to achieve sustainable treatment.
[0005] In electrocatalytic reduction, the core of the reaction lies in the active hydrogen species (H*). Active hydrogen gains electrons on the catalyst or electrode surface to generate highly reactive atomic hydrogen, possessing strong reducing power and capable of attacking nitro functional groups to achieve the conversion of -NO2 to -NH2. However, in traditional electrode systems, H* is often confined to the surface of the metal catalyst and struggles to migrate to regions far from the electrode surface. The hydrogen spillover effect effectively solves this problem, allowing H* to migrate from the metal site to the surface of adjacent supports and diffuse in the form of proton-electron pairs or coupled states, achieving a uniform reaction throughout the entire catalyst system and thus significantly improving the overall electrocatalytic degradation activity.
[0006] Currently, catalysts used for electrocatalytic H* production are mainly noble metal materials such as Pt, Pd, and Ru. While these materials exhibit high activity and rapid H* generation rates, they are also costly, resource-scarce, and prone to poisoning and deactivation in complex water systems, limiting their large-scale application in water pollution control. Therefore, developing efficient, stable, and economical non-noble metal active hydrogen catalysts has become a key research focus. Summary of the Invention
[0007] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing a Cu1 / CeO2 single-atom catalyst, the single-atom catalyst itself, and its applications. The single-atom catalyst prepared by the method exhibits excellent catalytic performance and good stability.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] This invention provides a method for preparing a Cu1 / CeO2 single-atom catalyst, comprising the following steps:
[0010] A carbon source, a foaming agent, a cerium source precursor, and a copper source are mixed and heated to react and obtain a Cu1 / CeO2 single-atom catalyst with oxygen vacancies supported on CeO2.
[0011] The subscript 1 for Cu in the Cu1 / CeO2 single-atom catalyst indicates that copper (Cu) exists as a "single, isolated metal atom" rather than as a cluster, nanoparticle, or bulk metal.
[0012] The preparation method described in this invention is based on CeO2, a reducible oxide support with strong oxygen storage and release capabilities. It achieves high dispersion and controllable coordination environment by anchoring single-atom metal sites, and utilizes the reversible valence state change and abundant oxygen vacancy structure on the support surface to construct active hydrogen migration channels, effectively triggering the hydrogen overflow effect and promoting the efficient diffusion of active hydrogen (H*) generated at the metal sites to various regions of the catalytic system.
[0013] The preparation method described in this invention not only constructs a two-dimensional CeO2 nanosheet structure with abundant porosity, but also firmly anchors single-atom copper (Cu1) onto the support surface, maximizing the exposure of catalytic active sites. Furthermore, this invention selects CeO2, a typical reducible oxide, as the support, leveraging the unique CeO2... 3+ / Ce 4+ Its reversible valence state transition property enables the in-situ generation and maintenance of abundant oxygen vacancies on its surface. These oxygen vacancies not only improve local electron transfer but also act as a "bridge" for hydrogen species migration, effectively triggering the hydrogen spillover effect. This allows the generated active hydrogen (H*) to migrate from the single-atom copper (Cu1) active site to the adjacent CeO2 support surface, greatly improving the utilization efficiency of active hydrogen and the overall electrocatalytic effect.
[0014] Preferably, the heating temperature is 600℃-800℃; more preferably, it is 700℃.
[0015] The present invention does not specifically limit the heating equipment described above; any heating equipment known to those skilled in the art, such as a muffle furnace or a tube furnace, is acceptable.
[0016] In some specific embodiments of the present invention, a muffle furnace is preferably used as the heating device.
[0017] The reaction in the above preparation method is carried out in an air atmosphere, and the heating holding time is 5-30 min, preferably 10 min.
[0018] The reactions in the method described in this invention include redox reactions and thermal decomposition reactions.
[0019] This invention involves uniformly mixing raw materials to obtain a powdered solid precursor mixture. The carbon source undergoes oxidation at high temperature, consuming local oxygen species and forming a transient, locally reducing microenvironment that promotes CeO2 surface Ce reduction. 4+ Partially converted to Ce 3+ This process is accompanied by the formation of oxygen vacancies, which also facilitates the atomic-level anchoring of copper species at defect sites. The foaming agent decomposes upon heating to produce gas, which acts as an in-situ gas template during its escape, causing the generated CeO2 to form a two-dimensional nanosheet structure with abundant pores.
[0020] In the above preparation method, the mixing is preferably achieved through grinding and mixing.
[0021] The present invention does not specifically limit the grinding equipment; any grinding equipment well known to those skilled in the art is acceptable.
[0022] In some specific embodiments of the present invention, the grinding equipment is preferably a mortar and pestle or a ball mill.
[0023] Heating the above solid precursor mixture causes redox reactions and thermal decomposition reactions.
[0024] After the reaction is complete, the mixture is cooled to room temperature in an air atmosphere, and the collected product is the Cu1 / CeO2 single-atom catalyst.
[0025] The preferred method for preparing the Cu1 / CeO2 single-atom catalyst of the present invention includes the following steps:
[0026] S1. Mix the carbon source, foaming agent (gas-generating aid), cerium source precursor and copper source, and perform solid-phase grinding to obtain a powdered solid precursor mixture;
[0027] S2. The powdered solid precursor mixture obtained in S1 is placed in a crucible, heated and kept at a certain temperature in a heating device, and the solid precursor mixture is thermally decomposed and redox reacted using the in-situ gas template method to prepare Cu1 / CeO2 single-atom catalyst (single-atom thin-film catalyst).
[0028] After the above thermal decomposition and redox reactions are completed, a cooling post-treatment is also included.
[0029] The heating equipment is naturally cooled to room temperature. The cooling process is carried out in an air atmosphere without the need for inert gas purging. The collected product is the Cu1 / CeO2 single-atom catalyst.
[0030] Preferably, the copper source of the present invention is selected from one or more of copper nitrate trihydrate, copper acetate, and copper chloride; more preferably, it is copper nitrate trihydrate.
[0031] Preferably, the cerium source precursor is selected from one or more of cerium nitrate, cerium chloride, and cerium acetate; more preferably, it is cerium nitrate hexahydrate.
[0032] Preferably, the foaming agent is selected from one or more of ammonium nitrate, ammonium bicarbonate, and melamine; more preferably, it is ammonium nitrate.
[0033] Preferably, the carbon source is selected from glucose, sucrose, fructose, citric acid, or cyclodextrin; more preferably, it is glucose.
[0034] Preferably, the mass ratio of the foaming agent to the cerium source precursor is (15-35):1; more preferably, it is 25:1.
[0035] Preferably, the mass ratio of the carbon source to the cerium source precursor is (10-30):1; more preferably, it is 20:1.
[0036] The preparation method described in this invention is simple to operate, the process is repeatable, and it is easy to scale up.
[0037] The present invention also provides a Cu1 / CeO2 single-atom catalyst, which is prepared by the above-described preparation method;
[0038] The Cu1 / CeO2 single-atom catalyst is composed of CeO2 and single-atom copper supported on its surface;
[0039] CeO2 is a two-dimensional nanosheet structure;
[0040] The specific surface area of CeO2 is 68.92 m² / g.
[0041] CeO2 has oxygen vacancies on its surface;
[0042] The theoretical loading of single-atom copper is preferably 1wt%-10wt%; more preferably 3wt%-8wt%; and even more preferably 5wt%.
[0043] In the single-atom catalyst of this invention, the oxygen vacancies and porous two-dimensional nanosheet structure of the CeO2 support synergistically interact with the single-atom copper sites: the porous two-dimensional structure facilitates the exposure of active sites and mass transfer, the oxygen vacancies facilitate the anchoring of single-atom copper and interfacial electronic regulation, and the single-atom copper sites promote the generation of active hydrogen. All three factors work together to promote the transfer and reduction of active hydrogen to nitro functional groups, thereby achieving efficient removal of nitro-based aromatic pollutants. Compared with traditional metal nanoparticle catalysts, the single-atom catalyst of this invention has significant advantages in the efficient denitrification conversion of nitro-based aromatic pollutants in water and the maintenance of catalytic performance.
[0044] The present invention also provides an electrode comprising a conductive substrate and the aforementioned Cu1 / CeO2 single-atom catalyst supported on its surface;
[0045] Preferably, the loading of Cu1 / CeO2 single-atom catalyst in the electrode is 0.1-1.5 mg / cm³. 2 More preferably 0.5-1 mg / cm³ 2 In some specific embodiments of the present invention, 0.67 mg / cm³ is preferred. 2 .
[0046] The conductive substrate includes, but is not limited to, carbon paper, carbon cloth, or carbon foam.
[0047] In some specific embodiments of the present invention, carbon paper is preferred.
[0048] Preferably, in this invention, the electrode further includes a perfluorosulfonic acid type ionomer;
[0049] Preferably, the perfluorosulfonic acid ionomer is selected from one or more of Nafion (perfluorosulfonic acid resin), Aquivion (perfluorosulfonic acid ionomer membrane), and Flemion (fluorine-containing cation exchange membrane); more preferably, it is Nafion. The present invention also provides a method for preparing the above-mentioned electrode, comprising the following steps: coating the dispersion of the above-mentioned Cu1 / CeO2 single-atom catalyst onto the surface of a conductive substrate, and drying to obtain the above-mentioned electrode;
[0050] Alternatively, the dispersion of the perfluorosulfonic acid ion polymer and the dispersion of the Cu1 / CeO2 single-atom catalyst according to claim 5 are mixed and coated onto the surface of a conductive substrate, and then dried to obtain the electrode according to claim 7.
[0051] Preferably, the concentration of Cu1 / CeO2 single-atom catalyst in the dispersion of the Cu1 / CeO2 single-atom catalyst prepared by the present invention is 0.5-6 mg / mL; more preferably 1-3 mg / mL; and even more preferably 2 mg / mL.
[0052] Preferably, in the dispersion of the Cu1 / CeO2 single-atom catalyst, the dispersion medium is a mixture of water and alcohol; in the dispersion of the perfluorosulfonic acid ionic polymer, the dispersion medium includes water, alcohol, or a mixture of water and alcohol; the specific dispersion medium is selected according to the specific perfluorosulfonic acid ionic polymer.
[0053] Preferably, the alcohol is selected from one or more of ethanol, n-propanol, and isopropanol; more preferably, it is ethanol.
[0054] In some specific embodiments of the present invention, the dispersion medium in the dispersion of the Cu1 / CeO2 single-atom catalyst is a mixture of water and ethanol;
[0055] Preferably, the volume ratio of ethanol to water in the mixture is (55-65):40; more preferably, it is 60:40.
[0056] The preferred method for preparing the above-mentioned electrode includes the following steps:
[0057] (1) The Cu1 / CeO2 single-atom catalyst is dispersed in an aqueous organic solvent and ultrasonically dispersed to form a uniform catalytic material dispersion;
[0058] (2) Add the dispersion of the ion polymer to the dispersion of the catalyst material, and sonicate to obtain an electrochemical slurry;
[0059] (3) The electrochemical slurry is coated on the surface of the pretreated conductive substrate and dried to form a working electrode.
[0060] The aqueous organic solvent is the mixture of water and alcohol mentioned above.
[0061] The ultrasonic dispersion time in step (1) is preferably 0.2-1 h, more preferably 0.5 h.
[0062] The drying temperature in step (3) is preferably 40℃-90℃; more preferably 55℃-75℃; and even more preferably 60℃.
[0063] The drying time is preferably 0.2-2 h; more preferably 0.5 h.
[0064] The pretreated conductive substrate in step (3) is obtained by ultrasonically cleaning the conductive substrate in an organic solvent and then briefly treating it in an acidic solution.
[0065] The purpose of ultrasonic cleaning is to remove surface impurities from the conductive substrate, and the purpose of short-time treatment is to remove the oxide layer on the surface of the conductive substrate and improve surface roughness.
[0066] The short-time treatment process involves immersing the ultrasonically cleaned conductive substrate in an acidic solution for 5-20 minutes.
[0067] The acidic solution includes, but is not limited to, hydrochloric acid, sulfuric acid, or nitric acid.
[0068] The present invention also provides a method for removing contaminants from water, comprising the following steps:
[0069] (1) The working electrode and the reference electrode are placed in the cathode chamber, and the counter electrode is placed in the anode chamber. The cathode chamber and the anode chamber are connected by an ion exchange membrane, a diaphragm or a salt bridge. The working electrode is the electrode described in claim 6 or 7, the reference electrode is a silver / silver chloride reference electrode, and the counter electrode is a metal anode.
[0070] (2) The working electrode, counter electrode and reference electrode are electrically connected to the electrochemical workstation to form a three-electrode electrochemical system;
[0071] (3) At a constant potential relative to the silver / silver chloride reference electrode, an electrochemical reduction reaction is carried out on the surface of the working electrode to remove the contaminants to be removed from the electrolyte in the cathode chamber.
[0072] Preferably, the constant potential is -1.4 to -1.1 V; more preferably, it is -1.2 to -1.1 V.
[0073] Preferably, the contaminant to be removed is selected from one or more of nitrobenzene, nitrobenzene, and nitrophenol.
[0074] Good NB (nitrobenzene) removal effects can be achieved within the above test potential range, with faster NB removal in the early stage of the reaction under the conditions of -1.1 V and -1.2 V.
[0075] Preferably, the electrolyte is a sulfate solution; more preferably, it is a sodium sulfate solution.
[0076] Preferably, the metal in the metal anode is selected from platinum, titanium, or stainless steel; more preferably, it is platinum.
[0077] In the method for removing pollutants from water according to the present invention, a platinum electrode is preferably used as the anode, and the cathode and reference electrode are placed in the electrolyte. The constant potential of the cathode relative to the reference electrode is controlled by an electrochemical workstation to achieve the electrochemical reduction and removal of the pollutants to be removed on the cathode surface.
[0078] The catalyst described in this invention significantly improves the generation efficiency and migration ability of active hydrogen through the synergistic effect of the metal (copper) single-atom sites and the reducible support (CeO2), and also enhances the selective reduction rate of nitro functional groups, reducing the possibility of side reactions. Furthermore, this catalyst structure exhibits excellent stability and durability during long-term water treatment.
[0079] Compared with existing technologies, the preparation method of Cu1 / CeO2 single-atom catalyst provided by this invention includes the following steps: mixing a carbon source, a foaming agent, a cerium source precursor, and a copper source, heating, and reacting to obtain a Cu1 / CeO2 single-atom catalyst with oxygen vacancies on a CeO2 support. In the preparation method of this invention, the carbon source participates in the high-temperature redox process and forms a local reducing microenvironment; the foaming agent decomposes upon heating to generate gas and acts as an in-situ gas template, thereby directly constructing a porous two-dimensional sheet structure with a high specific surface area; the oxygen vacancies and porous structure of the cerium dioxide support synergistically promote the generation, migration, and utilization of active hydrogen with single-atom copper sites. The preparation method is simple, time-saving, low-cost, and does not require a complex solvent system. The prepared catalyst exhibits extremely high removal efficiency (up to 100%) for nitro-aromatic pollutants in water, and has broad application prospects in the field of electrochemical treatment of environmental pollutants and industrial scale-up. Attached Figure Description
[0080] Figure 1 A schematic diagram of the process for preparing Cu1 / CeO2 catalyst and its application in removing nitrobenzene from water;
[0081] Figure 2 The X-ray diffraction (XRD) pattern of the Cu1 / CeO2 catalyst is shown.
[0082] Figure 3This is a scanning electron microscope (SEM) image of the Cu1 / CeO2 catalyst.
[0083] Figure 4 Transmission electron microscopy (TEM) image of Cu1 / CeO2 catalyst;
[0084] Figure 5 This is a high-resolution transmission electron microscope (HRTEM) image of the Cu1 / CeO2 catalyst. In the image, 0.31 nm and 0.27 nm represent lattice fringes with spacings of 0.31 nm and 0.27 nm, respectively.
[0085] Figure 6 High-resolution transmission electron microscopy (HRTEM) EDS image of Cu1 / CeO2 catalyst;
[0086] Figure 7 Image of Cu1 / CeO2 catalyst with aberration-corrected transmission electron microscopy (AC HAADF-STEM);
[0087] Figure 8 The X-ray photoelectron spectroscopy (XPS) high-resolution spectra of Cu1 / CeO2 single-atom catalysts are shown, where (a) is the 3d spectrum of Ce and (b) is the 1s spectrum of O.
[0088] Figure 9 The image shows the EPR spectrum of the Cu1 / CeO2 catalyst, with DMPO used as a probe.
[0089] Figure 10 The graphs show the change in NB removal rate over time during the electrochemical reduction degradation of nitrobenzene (NB) using Cu1 / CeO2 catalyst drop casting working electrodes prepared at different temperatures. The constant potential of the working electrode relative to the Ag / AgCl reference electrode is -1.2 V.
[0090] Figure 11 The graph shows the change in NB removal rate over time during the electrochemical reduction degradation of nitrobenzene (NB) by a Cu1 / CeO2 catalyst drop-cast working electrode under different applied voltage conditions. The concentration of sodium sulfate electrolyte was 0.1 mol / L, and the initial concentration of NB was 50 mg / L. Detailed Implementation
[0091] To further illustrate the present invention, the preparation method of the Cu1 / CeO2 single-atom catalyst provided by the present invention, the single-atom catalyst and its application are described in detail below with reference to the embodiments.
[0092] Example 1
[0093] Preparation of Cu1 / CeO2 catalyst
[0094] Accurately weigh 0.4 g of glucose (as carbon source and reducing agent), 0.5 g of ammonium nitrate (as gas-generating foaming agent), 0.02 g of cerium nitrate hexahydrate (Ce source), and 1.5 mg of copper nitrate trihydrate (Cu source, theoretical metal doping amount is 5 wt%). Place the above four solid precursors in an agate mortar and grind them thoroughly at room temperature. Continue grinding until the components are uniformly colored and the powder reaches a molecular-level uniform dispersion to obtain a mixture of solid precursors.
[0095] The uniformly ground precursor powder was transferred to a corundum crucible and placed in a muffle furnace. Under an air atmosphere, the furnace temperature was rapidly increased to 700 °C at a set heating rate and held constant for 10 min. During this short-duration high-temperature process, glucose participated in the redox process and formed a locally reducing microenvironment, while ammonium nitrate decomposed upon heating, releasing a large amount of gas. This in-situ gas generation process acted as a dynamic template, inducing the foaming and expansion of the generated cerium dioxide (CeO2) and its self-assembly to form a two-dimensional nanosheet structure with abundant porosity. Simultaneously, transition metal copper species, under the combined effect of defect sites and the locally reducing atmosphere, were firmly anchored on the CeO2 support surface in an atomically dispersed form.
[0096] After the heat preservation process is completed, the heating system is turned off, allowing the reaction system to cool to room temperature under natural atmosphere. This cooling process does not require purging with any inert gas. Once the furnace has completely cooled, the product in the crucible is collected, yielding the target product, the Cu1 / CeO2 single-atom thin-film catalyst.
[0097] Figure 1 A schematic diagram of the process for preparing Cu1 / CeO2 catalyst and its application in removing nitrobenzene from water;
[0098] Figure 2 The XRD pattern of the prepared Cu1 / CeO2 catalyst shows the characteristic diffraction peaks of CeO2, and no independent diffraction peaks of crystalline copper-containing species were detected, indicating that no distinguishable copper-containing crystalline phase was observed within the XRD detection limit; combined with Figure 7 The AC HAADF-STEM results further support the view that copper species are highly dispersed at isolated atomic sites.
[0099] Figure 3 The image shows a SEM image of the prepared Cu1 / CeO2 catalyst, indicating that a two-dimensional sheet structure with abundant pores was successfully synthesized.
[0100] Figure 4 TEM image of the prepared Cu1 / CeO2 catalyst.
[0101] Figure 5The image shows a high-resolution transmission electron microscope (HRTEM) image of the prepared Cu1 / CeO2 catalyst. The image clearly shows lattice fringes with spacings of 0.31 nm and 0.27 nm, which correspond to the (111) and (200) crystal planes of CeO2, respectively, indicating that the CeO2 crystal phase in the catalyst has good crystallinity.
[0102] Figure 6 The high-resolution transmission electron microscope (HRTEM) EDS image of the prepared Cu1 / CeO2 catalyst was obtained to identify the dispersion of Cu at the atomic level. The results showed that Cu, Ce and O elements were uniformly distributed in the material.
[0103] Figure 7 The image shows an aberration-corrected transmission electron microscope (AC HAADF-STEM) image of the prepared Cu1 / CeO2 catalyst. The image shows atomic sites anchored on the CeO2 lattice and distributed in isolation, indicating that the metallic copper in the catalyst is highly dispersed in the form of single atoms.
[0104] Figure 8 The XPS high-resolution spectrum of the prepared Cu1 / CeO2 single-atom catalyst is shown. The 3d spectrum of Ce, after peak fitting, also shows Ce. 3+ and Ce 4+ The characteristic components indicate the presence of Ce on the catalyst surface. 3+ / Ce 4+ Mixed valence states. The 1s spectrum of O can be decomposed into lattice oxygen (O). L ), defect-related oxygen (O) def ) and surface-adsorbed oxygen (O ads ) components, of which the defect-related oxygen component is related to Ce 3+ Species collectively support the presence of oxygen vacancies on the CeO2 surface.
[0105] Figure 9 The EPR spectrum of the prepared Cu1 / CeO2 catalyst is shown, with DMPO as a probe. Nine characteristic peaks corresponding to DMPO-H* were observed, indicating the presence of active hydrogen H* in the catalyst.
[0106] Application Example 1
[0107] Application of Cu1 / CeO2 catalyst drop-cast working electrode in electrochemical reduction degradation of NB
[0108] Two mg of the Cu1 / CeO2 single-atom catalyst prepared in Example 1 was dispersed in a mixture of ethanol and water at a volume ratio of 60:40, and then uniformly drop-coated onto a 3 cm thick substrate. 2The cathode was placed on a 1 cm × 3 cm piece of carbon paper, and the electrode was placed in a 0.1 M Na2SO4 solution (pH=6) containing 50 mg / L nitrobenzene.
[0109] Using a Cu1 / CeO2 catalyst-carbon paper electrode as the cathode, a platinum sheet as the anode, and silver / silver chloride as the reference electrode, a constant potential of -1.2 V relative to the Ag / AgCl reference electrode was applied, and the reaction was stirred at 300 rpm for 180 minutes.
[0110] Figure 10 The working electrode, prepared by drop casting of Cu1 / CeO2 catalysts obtained at different catalyst preparation temperatures, was used to measure the NB removal rate over time during the electrochemical reduction degradation of NB under a constant potential of -1.2 V relative to the Ag / AgCl reference electrode. The results showed that the Cu1 / CeO2 catalyst drop casting working electrode prepared at a catalyst preparation temperature of 700℃ at 180 min exhibited the best NB removal rate during the electrochemical reduction degradation of NB, approaching 100%.
[0111] Figure 11 The figures show the changes in NB removal rate over time under different applied potentials during the 180 min reaction. The results indicate that NB removal is relatively efficient after 180 min when the working electrode potential relative to the Ag / AgCl reference electrode is -1.1 V, -1.2 V, -1.3 V, and -1.4 V. In the early stage of the electrochemical reduction degradation of NB, the NB content decreases relatively rapidly under the -1.1 V and -1.2 V conditions. Considering both the NB removal rate and the low cathodic polarization, the optimal working electrode potential relative to the Ag / AgCl reference electrode is controlled between -1.2 V and -1.1 V.
[0112] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a Cu1 / CeO2 single-atom catalyst, characterized in that, Includes the following steps: A carbon source, a foaming agent, a cerium source precursor, and a copper source are mixed and heated to react and obtain a Cu1 / CeO2 single-atom catalyst with oxygen vacancies supported on CeO2.
2. The preparation method according to claim 1, characterized in that, The heating temperature is 600℃-800℃.
3. The preparation method according to claim 1 or 2, characterized in that, The copper source is selected from one or more of copper nitrate trihydrate, copper acetate, and copper chloride. The cerium source precursor is selected from one or more of cerium nitrate, cerium chloride, and cerium acetate; The foaming agent is selected from one or more of ammonium nitrate, ammonium bicarbonate, and melamine; The carbon source is selected from glucose, sucrose, fructose, citric acid, or cyclodextrin.
4. The preparation method according to claim 1, characterized in that, The mass ratio of the foaming agent to the cerium source precursor is (15-35):1; The mass ratio of the carbon source to the cerium source precursor is (10-30):
1.
5. A Cu1 / CeO2 single-atom catalyst, characterized in that, Prepared by the preparation method according to any one of claims 1-4; The Cu1 / CeO2 single-atom catalyst is composed of CeO2 and single-atom copper supported on its surface; CeO2 is a two-dimensional nanosheet structure; The specific surface area of CeO2 is 68.92 m² / g; CeO2 has oxygen vacancies on its surface; The theoretical loading of single-atom copper is 1wt%-10wt%.
6. An electrode, characterized in that, The Cu1 / CeO2 single-atom catalyst of claim 5 includes a conductive substrate and a Cu1 / CeO2 single-atom catalyst supported on its surface; The loading of Cu1 / CeO2 single-atom catalyst in the electrode is 0.1-1.5 mg / cm³. 2 .
7. The electrode according to claim 6, characterized in that, The electrode also includes a perfluorosulfonic acid type ion polymer; The perfluorosulfonic acid ionomer is selected from one or more of Nafion, Aquivion, and Flemion.
8. The method for preparing the electrode according to claim 6 or 7, characterized in that, The process includes the following steps: coating the dispersion of the Cu1 / CeO2 single-atom catalyst of claim 5 onto the surface of a conductive substrate and drying it to obtain the electrode of claim 6; Alternatively, the dispersion of the perfluorosulfonic acid ion polymer and the dispersion of the Cu1 / CeO2 single-atom catalyst according to claim 5 are mixed and coated onto the surface of a conductive substrate, and then dried to obtain the electrode according to claim 7. The concentration of Cu1 / CeO2 single-atom catalyst in the dispersion prepared by the method is 0.5-6 mg / mL. The dispersion medium in the dispersion of the Cu1 / CeO2 single-atom catalyst is a mixture of water and alcohol. The dispersion medium in the dispersion of the perfluorosulfonic acid ionic polymer includes water, alcohol, or a mixture of water and alcohol. The alcohol is selected from one or more of ethanol, n-propanol, and isopropanol.
9. A method for removing pollutants from water, characterized in that, Includes the following steps: (1) The working electrode and the reference electrode are placed in the cathode chamber, and the counter electrode is placed in the anode chamber. The cathode chamber and the anode chamber are connected by an ion exchange membrane, a diaphragm or a salt bridge. The working electrode is the electrode described in claim 6 or 7, the reference electrode is a silver / silver chloride reference electrode, and the counter electrode is a metal anode. (2) The working electrode, the counter electrode and the reference electrode are electrically connected to an electrochemical workstation to form a three-electrode electrochemical system. (3) At a constant potential relative to the silver / silver chloride reference electrode, an electrochemical reduction reaction is carried out on the surface of the working electrode to remove the contaminants to be removed from the electrolyte in the cathode chamber.
10. The method according to claim 9, characterized in that, The constant potential is -1.4 to -1.1 V; The contaminant to be removed is selected from one or more of nitrobenzene, nitrobenzene, and nitrophenol; The electrolyte is a sulfate solution; The metal in the metal anode is selected from platinum, titanium, or stainless steel.